1985
DOI: 10.1177/0148607185009002144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 15‐Hour Fat Infusions of Varying Dosage on Bilirubin Binding to Albumin

Abstract: Intravenous fat emulsions (1, 2, and 3 g/kg) were administered over 15 hr to 20 appropriate for gestational age premature infants with physiologic hyperbilirubinemia to determine the effect of fat infusions on the serum free fatty acid:albumin molar ratio (F/A) and on unbound bilirubin. Significant increases (p < 0.05) in F/A occurred with each increase in lipid dose in infants < 30 wk gestation, but not in infants ≥ 30 wk gestation. There was a direct linear correlation (r = 0.65, p < 0.001) between F/A ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…Neonatal HSA concentrations depend on gestational age, ranging from 280 to 470 mol/L (30 ). In neonates receiving Intralipid, FFA concentrations increase severalfold, resulting in substantial displacement of bilirubin from HSA and, therefore, large increases in B f concentrations (23,26,27 ). This variability in bilirubin-binding capacity can result in patients having similar plasma B T but different B f .…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal HSA concentrations depend on gestational age, ranging from 280 to 470 mol/L (30 ). In neonates receiving Intralipid, FFA concentrations increase severalfold, resulting in substantial displacement of bilirubin from HSA and, therefore, large increases in B f concentrations (23,26,27 ). This variability in bilirubin-binding capacity can result in patients having similar plasma B T but different B f .…”
Section: Discussionmentioning
confidence: 99%
“…Early lipid administration has been associated with chronic lung disease [19,20], whereas in other trials, no adverse effects were found [21,22,23,24]and even beneficial effects of lipids on lung development have been described [25]. It has also been hypothesized that fatty acids competitively bind to albumin and therefore cause an increase in free bilirubin or medication to dangerously high levels [26,27]. However, a small recent study shows that early lipid administration is safe and well tolerated.…”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%
“…Although previous studies have reported the postnatal concentrations of endogenous serum FFA in newborns, 7,8,29,30 little was known about serum FFA concentrations at 4-5 days of age, when serum TB peaks. We found that serum FFA and FFA/Alb ratio at 4 and 5 days of age were significantly lower at 1 day of age in term patients.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Although the impact of endogenous FFA has not been assessed directly, increased FFA has bilirubin displacing effects, especially in premature newborns receiving intravenous lipid supplementation for nutrition and growth. 7,9,10,28,33 At an FFA/Alb ratio 54, FFAs compete with bilirubin at the bilirubin binding site, resulting in the displacement of bilirubin. 7,8,10,27,28 We found that endogenous FFAs did not affect Alb binding of bilirubin, resulting in elevations of UB, since none of the sera, from both term and preterm infants, had FFA/Alb ratios 54.…”
Section: Discussionmentioning
confidence: 99%